Molecular identification of endophytic fungi from torch ginger (Etlingera elatior) antagonist to phytopathogenic fungi - Anisa Lutfia; Erman Munir; Yurnaliza Yurnaliza (Society for Indonesian Biodiversity, 2020)
Abstract. Lutfia A, Munir E, Yurnaliza. 2020. Molecular identification of endophytic fungi from torch ginger (Etlingera elatior) antagonist to phytopathogenic fungi. Biodiversitas 21: 2681-2689.  Medicinal plants are valuable sources in exploration of endophytic microorganisms. The utilization of culturable endophytes, particularly endophytic fungi in pharmacological aspects has been reported in many literature. Zingiberaceae, being known as one of medicinal plant families, is commonly used in tropical countries, e.g Indonesia to treat health disorders and ailments. However, little information has been reported upon their associative endophytic fungi that may be used as biocontrol agents against phytopathogenic fungi. Efforts to elaborate on the symbiotic relationship between endophytic fungi and host to explain the antifungal ability from endophytes are presented in this study. Six fungal morphotypes were recovered from the rhizome fragment of torch ginger (Etlingera elatior (Jack) RM Smith) sampled from Sibayak forest, North Sumatra, Indonesia. All isolates displayed potential antifungal activities against Fusarium oxysporum, Ganoderma boninense, and Rigidoporus lignosus as representative phytopathogens in a dual culture plate assay. All fungal morphotypes were identified based on their 18S rDNA-ITS regions. Molecular identification revealed that most isolates were related to Trichoderma spp. while one isolate was identified as Pestaliotopsis sp. The endophytic assemblage of mostly Trichoderma strains in our study may reveal a mutual relationship of these soil fungi as root colonizer displaying biocontrol properties against phytopathogenic fungi to host.